A arthur ohlsten Full Member Joined Feb 20, 2005 Messages 854 Jul 20, 2005 #2 1/m +1/n=k subtract 1/m from each side 1/n = k - 1/m place right side over common denominator m 1/n = [km -1]/m multiply both sides n 1= n [km-1] /m multoply both sides by m m=n[km-1] divide both sides by km-1 m/[km-1] =n answer Arthur

1/m +1/n=k subtract 1/m from each side 1/n = k - 1/m place right side over common denominator m 1/n = [km -1]/m multiply both sides n 1= n [km-1] /m multoply both sides by m m=n[km-1] divide both sides by km-1 m/[km-1] =n answer Arthur

D Denis Senior Member Joined Feb 17, 2004 Messages 1,465 Jul 20, 2005 #3 really lost said: :? 1/m+1/n=k solve for n Click to expand... Another way; your equation is: 1/m + 1/n = k multiply it by m: 1 + m/n = km m/n = km - 1 n = m / (km - 1) Same thing, but start by isolating the term with n: 1/n = k - 1/m now multiply by m: m/n = km - 1 n = m / (km - 1)

really lost said: :? 1/m+1/n=k solve for n Click to expand... Another way; your equation is: 1/m + 1/n = k multiply it by m: 1 + m/n = km m/n = km - 1 n = m / (km - 1) Same thing, but start by isolating the term with n: 1/n = k - 1/m now multiply by m: m/n = km - 1 n = m / (km - 1)